ANALISIS EFEKTIVITAS GAME-BASED LEARNING DAN PARTISIPASI SISWA DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DI KELAS X SMK DWI WARNA MEDAN - Wina Mutiara Eristina Purba; Evi Susilawati; Sapta Kesuma (Jurnal Genta Mulia, 2026)
This study aims to analyze the effectiveness of using Game Based Learning in increasing the motivation of tenth-grade students at SMK Dwi Warna Medan in Civics subjects, and to examine the impact of implementing Game Based Learning on student participation during the Civics learning process. This research uses a quantitative approach with a quasi-experimental design. The data and data sources in this study are the respondents and other sources that support this research. Data management is carried out using instruments consisting of pre-test and post-test questions. Data analysis in this study uses statistical tests such as normality test, homogeneity test, and paired sample t-test. This is evidenced by the comparison of pre-test and post-test scores, which showed a significant increase. The average pre-test score of students in the experimental group was recorded at 66.00, while the post-test score reached 87.60, indicating an increase of 21.6 points. Based on the paired t-test results, the significance value obtained was p = 0.000 (p < 0.05), which means there is a statistically significant difference between the learning outcomes before and after using the Game-Based Learning (GBL) method. Based on the questionnaire results given before and after the treatment, student participation increased from an average pre-test score of 64.96 to 76.48 in the post-test. This increase of 11.52 points shows that the game-based learning method can encourage students to be more active in discussions, answering questions, and participating in educational games embedded in the learning material.